CORRELATION BETWEEN TEACHER SKILLS IN MANAGING CLASSES WITH PHYSICS LEARNING ACHIEVEMENT - Fauziah, Rizka; Rustana, Cecep E.; Raihanati, Raihanati (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
Student learning achievement are affected by internal and external factors. Teacher skills in managing class is one of the external factor that would be effect students learning achievement. The purpose of this study is to determine the correlation between teacher skills in managing classes with physics learning achievement of class XI IPA of SMA Negeri 1 Jakarta. The survey research with the correlational approach was applied to 64 students that was randomly sampled from all student population of class XI IPA of SMA Negeri 1 Jakarta. The data that was collected using questionnaires and documentation were statistically analyzed using regression and correlation techniques. Based on the results of the study, it can be concluded that there is no correlation between teacher skills in managing classes with student physics learning achievement of Class XI IPA of SMA Negeri 1 Jakarta